For-profit long-term care homes and the risk of COVID-19 outbreaks and resident deaths - Stall, Nathan M.; Jones, Aaron; Brown, Kevin A.; Rochon, Paula A.; Costa, Andrew P. (Canadian Medical Association journal (CMAJ), 2020)
Long-term care (LTC) homes have been the epicentre of the coronavirus disease 2019 (COVID-19) pandemic in Canada to date. Previous research shows that for-profit LTC homes deliver inferior care across a variety of outcome and process measures, raising the question of whether for-profit homes have had worse COVID-19 outcomes than nonprofit homes. We conducted a retrospective cohort study of all LTC homes in Ontario, Canada, from Mar. 29 to May 20, 2020, using a COVID-19 outbreak database maintained by the Ontario Ministry of Long-Term Care. We used hierarchical logistic and count-based methods to model the associations between profit status of LTC homes (for-profit, nonprofit or municipal) and COVID-19 outbreaks in LTC homes, the extent of COVID-19 outbreaks (number of residents infected), and deaths of residents from COVID-19. The analysis included all 623 Ontario LTC homes, comprising 75 676 residents; 360 LTC homes (57.7%) were for profit, 162 (26.0%) were nonprofit, and 101 (16.2%) were municipal homes. There were 190 (30.5%) outbreaks of COVID-19 in LTC homes, involving 5218 residents and resulting in 1452 deaths, with an overall case fatality rate of 27.8%. The odds of a COVID-19 outbreak were associated with the incidence of COVID-19 in the public health unit region surrounding an LTC home (adjusted odds ratio [OR] 1.91, 95% confidence interval [CI] 1.19–3.05), the number of residents (adjusted OR 1.38, 95% CI 1.18–1.61), and older design standards of the home (adjusted OR 1.55, 95% CI 1.01–2.38), but not profit status. For-profit status was associated with both the extent of an outbreak in an LTC home (adjusted risk ratio [RR] 1.96, 95% CI 1.26–3.05) and the number of resident deaths (adjusted RR 1.78, 95% CI 1.03–3.07), compared with nonprofit homes. These associations were mediated by a higher prevalence of older design standards in for-profit LTC homes and chain ownership. For-profit status is associated with the extent of an outbreak of COVID-19 in LTC homes and the number of resident deaths, but not the likelihood of outbreaks. Differences between for-profit and nonprofit homes are largely explained by older design standards and chain ownership, which should be a focus of infection control efforts and future policy.